2019
DOI: 10.3390/toxins12010014
|View full text |Cite
|
Sign up to set email alerts
|

Extending Metabolomic Studies of Apis mellifera Venom: LC-MS-Based Targeted Analysis of Organic Acids

Abstract: Organic acids are important active small molecules present in venoms and toxins, which have not been fully explored yet. The aim of the study was the determination of organic acids in honeybee venom (HBV) samples by using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Two protocols for sample preparation were employed. A solid-phase extraction was used for the determination of malonic acid, fumaric acid, glutaric acid, and kynurenic acid. A dilute-and-shoot method was optimal for: citric acid, mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…The range of the measured metabolites lacked organic acids, which is an important metabolite class present in animal venoms 42 . However, the profiles of low-molecular-weight organic acids have already been studied by our team 18 . The study demonstrated that citric acid was the most abundant acid in HBV and constituted at least 7.3% of the venom dry weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of the measured metabolites lacked organic acids, which is an important metabolite class present in animal venoms 42 . However, the profiles of low-molecular-weight organic acids have already been studied by our team 18 . The study demonstrated that citric acid was the most abundant acid in HBV and constituted at least 7.3% of the venom dry weight.…”
Section: Discussionmentioning
confidence: 99%
“…To date, modern metabolomics platforms have rarely been used in venom studies, including HBV 17 . Recently, we have conducted the determination of a panel of organic acids in HBV using liquid chromatography-tandem mass spectrometry-based method 18 . Nonetheless, there is still a lack of detailed studies on the determination of such significant groups of metabolites as free amino acids or lipids.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 11 studies were published. Three reviews provided a good overview of the therapeutic effect of bee venom [ 6 , 7 , 8 ], and eight original research articles focused on bee venom, melittin, PLA 2 , and apamin [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
mentioning
confidence: 99%
“…Finally, two studies focused on the whole honeybee venom. Pawlek et al [ 15 ] demonstrated that citric acid was the most abundant acid, whereas glutaric acid and kynurenic acid were the lowest organic acids present in the honeybee venom. A review study by El-Seedi et al [ 7 ] focused on the antimicrobial properties of honeybee venom.…”
mentioning
confidence: 99%
“…The fragment ions of these three compounds were generated by losing the –CO 2 group. Therefore, they were tentatively identified as fumaric, itaconic, and succinic acids [ 49 , 50 , 51 ]. Compound 3 lost an –H 2 O group from the precursor ion m/z 133 and was tentatively identified as malic acid [ 49 ].…”
Section: Resultsmentioning
confidence: 99%